Assessment of Training Quality Management According to "Total Quality Management" Model at Vietnam National University, Hanoi - International School - Nguyen, Quang; Vu Ngoc, Tu (VNU Journal of Science: Policy and Management Studies, 2017)
The application of the "Total Quality Management" model (TQM) in quality management and accreditation has been adopted by many countries in the world, but in Vietnam it is still quite new. To investigate and study the applicability and evaluation of general management and training quality management in particular according to TQM in order to propose practical suggestions to the International School, Vietnam National University, Hanoi (VNU), the authors have conducted a survey of 168 students (25 first-year students, 53 second-year students, 51 third-year students, 39 fourth-year students); 23 teaching and management staff. The results indicate that the current training quality management is evaluated to be average by students and quite good by teaching and management staff. All the students and staff argue that the implementation of training quality management according to TQM criteria is feasible.